Potensi Kayu Rakyat dan Strategi Pengembangannya (Studi Kasus) di Hutan Rakyat Desa Buana Sakti Kecamatan Batanghari Kabupaten Lampung Timur - Tri Putri Siadari; Rudi Hilmanto; Wahyu Hidayat (Department of Forestry, Faculty of Agriculture, University of Lampung, 2013)
This study aims to determine the potential of timber from private forest and to analyze the strategy to develop the management of private forest in Buana Sakti.This research held at March-May 2012. Tree data and timber potency were collected by using measurement plot of 20x20m with sampling intensity of 1%.The datas were then analyzed quantitatively. SWOT analysis is performed to determine the proper development strategy of private forest in Buana Sakti. The results show that the potential of timber in private forest of Buana Sakti is 111,79 m3 which comprise of timber teak, rubber, randu, jengkol, sengon, sonokeling, acacia, waru, clove, melinjo with the potential revenue of Rp. 159.959.000/ha. The calculations show that the INP most dominant plant species are acacia that is equal to 88,18% with 51,88% of total KR, FR 28,95%, 7,35% DR. The development strategy of private forest that needed to be applied are selecting the best quality and provide education to farmers about the important of forest. Keywords: forestry, strategy development, wood forest products